A novel enantioselective synthesis of allenic esters and amides - Apsimon, Megan K (University of Ottawa (Canada), 2009)
In recent years, allenes have become recognized as useful synthons in organic chemistry. Their unique orthogonal pi-bond system can be used in a variety of regio- and stereoselective carbon-carbon bond-forming reactions. Chiral allenes also have the ability to transfer their chirality to one or more new chiral centres. Despite this usefulness, the synthesis of chiral allenes is quite limited. Most methods to synthesize asymmetric allenes require chirality transfer from a pre-formed chiral centre, while only a handful of methods exists which form an asymmetric allene from achiral starting materials. We have discovered a new method for synthesizing chiral allenes using achiral 3-alkynoates or 3-alkynamides. Treatment of a propargyl carbonyl compound with a catalytic silver source and a chiral Lewis Acid in the presence of a weak amine base results in the formation of chiral allenic esters and amides. Initial reactions with 3- alkynoates lead to the discovery of AgSbF6 and (R)-(S)-JOSIPHOS as the ideal catalyst system, and N-methylmorpholine as the base. When the reaction was performed in a mixture of methanol/THF, this resulted in the formation of allenes with ee values higher than 90%. The reactions did not complete, however, resulting in a mixture of alkynes and allenes which was not separable by chromatography. This problem was solved by applying the same methodology to 3-alkynamides. Within an hour at 0°C, the reaction was finished, and the alkynes and allenes could easily be separated chromatographically. Nine different allenic amides were synthesized, in 27-95% yield, and 90-99% ee. Once the allenes were synthesized, we determined the absolute stereochemistry, discovering that our methodology formed the (S)-allenes. We did this by transforming the allenes to a known butenolide via and iodolactionization reaction and removal of the iodine. By comparing the experimental optical rotation to the known optical rotation, we were able to determine the absolute stereochemistry. This was also confirmed by applying the Lowe-Brewster rule, a rule which applies only to allenes. In allenes, the absolute stereochemistry and axial helicity of the compound can be used to predict the direction of the optical rotation, and vice versa.
Keywords: Chemistry, Organic.